Effects of dietary α-ketoglutarate supplementation on growth performance, digestive enzyme activity, immune gene expression, and intestinal morphology of largemouth bass (Micropterus salmoides) fed high soybean diet - Dujuan Zheng; Xin Yang; Jun Liang; Jianhua Zhao; Qiyou Xu (Aquaculture Reports)
This study investigated the effects of α-ketoglutarate (AKG) on the growth performance, intestinal health, and immune gene expression in largemouth bass (Micropterus salmoides). Largemouth bass with an initial weight of 25.5 ± 0.5 g was fed for 8 weeks with three isonitrogenous and isolipidic diets, each with three replicates, and 20 fish per replicate. The control diet contained 41.30 % soybean meal (SM) group, while the experimental diets were supplemented with 1.00 % (AKG1) and 2.00 % (AKG2) AKG. The results showed that AKG had no significant effects on growth performance, body composition, or the gene expression of AMPK-α, 4E-BP, TGFβ1, and TGFβ2 (P > 0.05). However, compared to the SM group, the AKG1 group significantly increased the α-amylase and trypsin activities in the foregut (P < 0.05). Additionally, lipase and trypsin activities in the midgut and hindgut were increased in the AKG2 group, while α-amylase activity in these regions was significantly decreased (P < 0.05). Both AKG groups significantly increased intestinal mucosal thickness and villus height, and significantly decreased crypt depth (P < 0.05). Additionally, the AKG groups reduced the gene expression of intestinal ACC, caspase-3, caspase-8, caspase-9, and IL-1β, whereas TOR expression was significantly increased and TNF-α expression decreased in the AKG2 group (P < 0.05). Therefore, supplementation with 1–2 % AKG can alleviate the negative effects of soybean meal on intestinal apoptosis and inflammation, thereby enhancing intestinal health.